2020
DOI: 10.1126/scitranslmed.aaz6667
|View full text |Cite
|
Sign up to set email alerts
|

Combination of metabolic intervention and T cell therapy enhances solid tumor immunotherapy

Abstract: Treatment of solid tumors with T cell therapy has yielded limited therapeutic benefits to date. Although T cell therapy in combination with proinflammatory cytokines or immune checkpoints inhibitors has demonstrated preclinical and clinical successes in a subset of solid tumors, unsatisfactory results and severe toxicities necessitate the development of effective and safe combinatorial strategies. Here, the liposomal avasimibe (a metabolism-modulating drug) was clicked onto the T cell surface by lipid insertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 56 publications
1
59
0
Order By: Relevance
“…SOAT1 was genetically knocked out of the T-cells of mice rather than in the implanted B16F10 cells and interestingly produced a similar standardised mean difference in tumour volume to systemic avasimibe treatment [62]. Furthermore, the introduction of T-cells and avasimibe to lymphodepleted mice led to significantly smaller tumours than treatment with avasimibe alone [61]. Interestingly, animals from this study were treated with just 2 mg/kg avasimibe, considerably lower than the doses we found reported in other studies of skin, or any other cancer type.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SOAT1 was genetically knocked out of the T-cells of mice rather than in the implanted B16F10 cells and interestingly produced a similar standardised mean difference in tumour volume to systemic avasimibe treatment [62]. Furthermore, the introduction of T-cells and avasimibe to lymphodepleted mice led to significantly smaller tumours than treatment with avasimibe alone [61]. Interestingly, animals from this study were treated with just 2 mg/kg avasimibe, considerably lower than the doses we found reported in other studies of skin, or any other cancer type.…”
Section: Resultsmentioning
confidence: 99%
“…Skin cancers (melanoma and non-melanoma) are the third most prevalent cancer type in the world [49]. Tumour burden was significantly lower in models of skin cancer that had been treated with SOAT1 inhibitors across all four studies relevant for quantitative analysis [53,[60][61][62] (SMD = -3.61; 95% CI: -4.55 to -2.67; I 2 = 25%; p < 0.00001; Fig4E). SOAT1 was genetically knocked out of the T-cells of mice rather than in the implanted B16F10 cells and interestingly produced a similar standardised mean difference in tumour volume to systemic avasimibe treatment [62].…”
Section: Skin Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…It increases the plasma membrane cholesterol content, thereby promoting TCR aggregation and improving the T cell function [151]. Hao et al used click chemistry to attach Ava-containing nanoliposomes to the surface of engineered T cells without interfering with their physiological functions [26]. Finally, studies have shown that TCR transgenic CD8 + T cells and chimeric antigen receptor T cells carrying liposomal AVA have good antitumor effects in mouse models of melanoma and glioblastoma [152].…”
Section: Nanoparticle-based Strategies For Melanoma Immunotherapymentioning
confidence: 99%
“…Drug resistance is an important characteristic of melanoma, resulting in the lack of effectiveness of current drug treatments [17][18][19][20][21]. Surgery [22,23], chemotherapy [24,25], and immunotherapy [26,27] are the most commonly approaches. However, these treatments are largely limited by an advanced cancer diagnosis, off-target drug delivery and concentration, systemic toxicity, and drug-induced undesirable side effects.…”
Section: Introductionmentioning
confidence: 99%